Vaginal Administration of Contraceptives - Esmat Jalalvandi; Hafez Jafari; Christiani A. Amorim; Denise Freitas Siqueira Petri; Lei Nie; Amin Shavandi (MDPI AG, 2020)
While contraceptive drugs have enabled many people to decide when they want to have a baby, more than 100 million unintended pregnancies each year in the world may indicate the contraceptive requirement of many people has not been well addressed yet. The vagina is a well-established and practical route for the delivery of various pharmacological molecules, including contraceptives. This review aims to present an overview of different contraceptive methods focusing on the vaginal route of delivery for contraceptives, including current developments, discussing the potentials and limitations of the modern methods, designs, and how well each method performs for delivering the contraceptives and preventing pregnancy.